Sadapan Lewis: Mengungkap Gelombang P yang Tersembunyi - Harmoko, Afandi Dwi; Sulastomo, Heru (The Indonesian Heart Association, 2021)
Background. The Lewis lead configuration can help to detect atrial activity and its relationship to ventricular activity, so diagnosis can be achieved more accurately. With Lewis lead ECG, it will make easier to make a diagnosis, especially in identifying electrical activity in the atrium. Case Illustration. Case 1. A 61-year-old male with decreased consciousness et causa metabolic. From a standard 12-lead ECG, the P waves are difficult to identify, and at first glance it looks like atrial fibrillation. From the Lewis ECG in lead I, it appears that the QRS wave is always preceded by a P wave, with different morphologies (more than 3 forms), that showed as multifocal atrial tachycardia (MAT) with a heart rate of 120 beats / minute. Case 2. The 58-year-old male patient complained of typical ischemic chest pain and palpitations. A standard 12 lead ECG examination revealed a rhythmic tachycardia with a wide QRS wave at a rate of 210 beats / minute. From the Lewis ECG in lead I, we can see that the P waves that appear are not always followed by QRS. Thus, it can be seen that the AV dissociation is a VT so that VT management can be done immediately. Case 3. A 65-year-old male patient diagnosed with grade 5 CKD on dialysis. From a standard 12 lead ECG examination, a wide QRS wave with a P wave is obtained which is sometimes seen behind the QRS wave, making the diagnosis difficult to establish. From the Lewis ECG in lead I, it appears that the P wave always appears at the end of the QRS wave, so it can be seen that the rhythm from the ECG is derived from accelerated idioventricular rhythm with ventriculoatrial conduction. Conclusion. The accuracy of ECG interpretation is needed to determine the next treatment for the patient. Through the ECG examination with the Lewis lead method, the cardiac electrical activity will be more visible, so it will be very helpful in the interpretation of the ECG in cases that are not clear on the standard 12 lead ECG examination.